Age and Gender Difference in the Association of Metabolic Syndrome and Peripheral Artery Disease Among Patients With Type 2 Diabetes Mellitus - Xiaotong Feng; Yongsong Xu; Lin Zhu; Kun Li; Lin Mao; Huan Dong; Dong Zhao; Jing Ke (International Journal of Vascular Medicine)
Conclusions: In summary, our findings suggest that the risk of PAD is positively correlated with the number of MetS components in patients with T2DM, especially among younger patients and older patients. Additionally, the positive association between the number of MetS components and the presence of PAD was significantly more evident in female patients.